Rights based approaches to development in Ethiopia : theory, application and power dynamics - Ferguson, Hanna (2009)
The purpose of this thesis is to explore aspects of rights based approaches to development. Particularly the aim is to describe how power works in and through the approach – on the theoretical and practical levels. The different dimensions are explored using the theories on power as they relate to power over, to, with and within. The empirical data was collected by interviewing organisations in Ethiopia who utilizes rights based approaches in their work. The snowball method was used to get informants and the focused .interview method to talk to the informants. All together 11 in depth interviews were carried out. The data is analysed through methods suitable for qualitative research. The data revealed that there is a gap in rights based theory and practice. On a theoretical level, rights based approaches challenge oppressive power over by promoting participation, accountability and empowerment. Yet, many of the ideas promoted at the theoretical level are not lived out in practice. Power relations are challenged, but not transformed. The data showed that local organizations struggle to implement the approach and instead of being empowered by it, many are left feeling disempowered, and vulnerable.